Buprestidae (Coleoptera) from Oaxaca State, Mexico - Reyes-González, Roberto; Rös, Matthias; Martínez-Hernández, José Guadalupe; Corona-López, Angélica María (Zootaxa, 2024)
A checklist with 246 species, three subspecies, 37 genera, 19 tribes, and four subfamilies of Buprestidae and their distribution in the state of Oaxaca is provided. Acmaeodera crossi Barr, 1992, Chrysobothris viridiimpressa Gory & Laporte, 1837 and Melanophila atra Gory, 1841 are recorded for the first time in the state. Leucaena esculenta (DC.) Benth and Vachellia pennatula (Schltdl. & Cham.) Seigler & Ebinger, are recorded as new adult host plants for two buprestid species in Mexico.